Iron Oxide Nanoparticle-Incorporated Mesenchymal Stem Cells for Alzheimer’s Disease Treatment - Jung, Mungyo; Kim, Hyeongseop; Hwang, Jung Won; Choi, Yejoo; Kang, Mikyung; Kim, Cheesue; Hong, Jihye; Lee, Na Kyung; Moon, Sangjun; Chang, Jong Wook; Choi, Suk-joo; Oh, Soo-young; et al. (Nano letters, 2023)
Alzheimer’s disease (AD) is a neurodegenerative disease with multifactorial pathogenesis. However, most current therapeutic approaches for AD target a single pathophysiological mechanism, generally resulting in unsatisfactory therapeutic outcomes. Recently, mesenchymal stem cell (MSC) therapy, which targets multiple pathological mechanisms of AD, has been explored as a novel treatment. However, the low brain retention efficiency of administered MSCs limits their therapeutic efficacy. In addition, autologous MSCs from AD patients may have poor therapeutic abilities. Here, we overcome these limitations by developing iron oxide nanoparticle (IONP)-incorporated human Wharton’s jelly-derived MSCs (MSC-IONPs). IONPs promote therapeutic molecule expression in MSCs. Following intracerebroventricular injection, MSC-IONPs showed a higher brain retention efficiency under magnetic guidance. This potentiates the therapeutic efficacy of MSCs in murine models of AD. Furthermore, human Wharton’s jelly-derived allogeneic MSCs may exhibit higher therapeutic abilities than those of autologous MSCs in aged AD patients. This strategy may pave the way for developing MSC therapies for AD.